Internalization of Islamic Value-Based Character Education in the Daily Lives of Madrasah Ibtidayah Students - Choirul Anam; Novia Rosyidah Hidayati Ali (Tarsib: Jurnal Program Studi PGMI, 2026)
This study aims to describe the process of internalizing Islamic value-based character education in the daily lives of students at Madrasah Ibtidayah (MI) Islamiyah Ngoro Jombang. The background of this study is based on the importance of strengthening religious character amidst the challenges of globalization and technological developments that impact student behavior. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, in-depth interviews, and documentation, with research subjects including the madrasah principal, teachers, and students. The results show that internalization of Islamic values ​​is carried out through several strategies, namely teacher role models (uswah hasanah), habituation of religious activities such as congregational prayer, reading the Qur’an, and other religious activities, and integration of character values ​​in the classroom learning process. In addition, a conducive madrasah environment and support from parents also strengthen the internalization process. The dominant character values ​​instilled in students include religiosity, discipline, responsibility, and politeness. However, this study also identified several obstacles, including differences in students’ family backgrounds, influences from the environment outside the madrasah, and limited supervision outside of school hours. Therefore, synergy between madrasahs, families, and the community is needed to continuously strengthen Islamic values-based character education.